Pengaruh Hubungan Istimewa dan Good Corporate Governance terhadap Kebijakan Deviden dengan Manajemen Laba Sebagai Variabel Intervening pada Perusahaan Manufaktur yang Terdaftar di Bursa Eefek Indonesia Tahun 2016-2021 - Muhamad Saleh; Arna Suryani; Ali Akbar (Universitas Batanghari, 2023)
This study aims to: 1) identify, describe and analyze the effect of special relationships on earnings management; 2) the effect of good corporate governance on earnings management; 3) the effect of special relations on dividend policy; 4) the effect of good corporate governance on dividend policy; 5) the effect of earnings management on dividend policy; 6) the influence of special relationships and earnings management on dividend policy; and 7) the effect of good corporate governance and earnings management on dividend policy in manufacturing companies listed on the IDX for the 2016-2021 period.. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange totaling 172 companies. The researcher chose a purposive sampling technique by setting certain considerations or criteria that must be met by the samples used in this study, the samples in this study totaled 25 manufacturing companies that met the predetermined sample criteria. To answer the research objectives, the researcher uses a quantitative research method with a descriptive approach and path analysis (Path Analysis) using the help of SmartPLS (outer model and inner model). The research results show that: 1) special relationship has a significant effect on earnings management; 2) good corporate governance has no significant effect on earnings management; 3) special relationship does not have a significant influence on dividend policy; 4) good corporate governance has a significant influence on dividend policy; 5) Earnings management has a significant influence on dividend policy; 6) there is influence of special relationship and earnings management on dividend policy; and 7) there is no significant influence between good corporate governance and earnings management on dividend policy.